2018
DOI: 10.1177/0003489418769942
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Recovery in Pediatric Sudden Sensorineural Hearing Loss Predicted via Magnetic Resonance Imaging

Abstract: The potential recovery of hearing in children raises concerns about very early surgical intervention within the first 6 months. Rational imaging and sequential audiometric evaluation to monitor the progression of recovery may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…One was excluded due to inconsistencies within the article in the number of patients with hearing recovery 5 . The other was excluded because of overlap in the patient population and data presented in this article 25 and those presented in a more comprehensive included article 7 . Consequently, 13 studies were included in final qualitative and quantitative analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One was excluded due to inconsistencies within the article in the number of patients with hearing recovery 5 . The other was excluded because of overlap in the patient population and data presented in this article 25 and those presented in a more comprehensive included article 7 . Consequently, 13 studies were included in final qualitative and quantitative analyses.…”
Section: Resultsmentioning
confidence: 99%
“…5 This made it unreliable to extract the appropriate numbers to insert into our meta-analysis. One other study 25 was excluded because it reported outcomes for a subset of patients that were reported more comprehensively in another included study. 7 Therefore, 13 studies were identified as appropriate for inclusion.…”
Section: Study Characteristicsmentioning
confidence: 99%